1993
DOI: 10.1002/app.1993.070500312
|View full text |Cite
|
Sign up to set email alerts
|

Study of the thermal degradation of poly(N‐vinyl‐2‐pyrrolidone) by thermogravimetry–FTIR

Abstract: SYNOPSISThe thermal degradation of poly (N-vinyl-2-pyrrolidone) (PVP) was studied by dynamic thermogravimetric analysis (TGA) in the range 200-600°C under nitrogen and oxygen atmospheres a t various heating rates. The apparent activation energy of the degradative process was determined by the application of kinetic treatments, giving an average value of 242 kj/mol in Nz, whereas in the presence of oxygen, two trends may be considered At relatively low temperatures (200-400°C) and degrees of conversion, a, lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
70
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 11 publications
13
70
0
Order By: Relevance
“…To our knowledge, only two papers have dealt with the analysis of the possible degradation products [18,19]. These studies revealed the formation of pyrrolidone [18] or a mixture of pyrrolidone and N-vinylpyrrolidone [19] as the main pyrolytic products of pure PVP and, therefore, support our observations.…”
Section: Pyrolytic Products Reproducibility Linearity and Sensitivitysupporting
confidence: 86%
See 2 more Smart Citations
“…To our knowledge, only two papers have dealt with the analysis of the possible degradation products [18,19]. These studies revealed the formation of pyrrolidone [18] or a mixture of pyrrolidone and N-vinylpyrrolidone [19] as the main pyrolytic products of pure PVP and, therefore, support our observations.…”
Section: Pyrolytic Products Reproducibility Linearity and Sensitivitysupporting
confidence: 86%
“…To our knowledge, only two papers have dealt with the analysis of the possible degradation products [18,19]. These studies revealed the formation of pyrrolidone [18] or a mixture of pyrrolidone and N-vinylpyrrolidone [19] as the main pyrolytic products of pure PVP and, therefore, support our observations. Noteworthy, thermal degradation of PVP adsorbed on the surface of pyrogenic silica showed a pronounced dependence between the amount of the adsorbed polymer and the relative distribution of both degradation products, 2-Py and NVP [19].…”
Section: Pyrolytic Products Reproducibility Linearity and Sensitivitysupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, PVP is thermally degraded, predominantly, by the release of the pyrrolidone side group and the subsequent decomposition of polyenic sequences [27]. In inert atmosphere those polyenic sequences, undergoing to condensation reaction, may lead to the formation of a certain amount of carbonaceous residue.…”
Section: Characterization Of Tio 2 Samples Obtained By Electrospinningmentioning
confidence: 99%
“…All thermograms showed two distinct zones, ascribed to the degradation of the PLGA and PVP portions, with a decomposition temperatures at 5% weight loss of 308 8C and 387 8C, respectively, in line with the values normally reported for the virgin polymers. 32,33 Passing from PLGA-g-PVP 10:1 to PLGA-g-PVP 10:2 and PLGA-g-PVP 10:3 the thermograms showed the expected increase of the PVP-related portions. The TGA estimates of the wt% PVP, namely 5.0, 13.2, and 21.9 were fairly consistent with the IR assessments.…”
Section: Thermal Analysismentioning
confidence: 92%